2018
DOI: 10.3892/etm.2018.5859
|View full text |Cite
|
Sign up to set email alerts
|

Expression of serum AMPD1 in thyroid carcinoma and its clinical significance

Abstract: This study investigated the expression of adenosine monophosphate deaminase 1 (AMPD1) in serum of patients with papillary thyroid carcinoma (PTC) and its clinical significance. The expression levels of AMPD1 mRNA in serum of 157 patients with PTC and 100 normal controls were detected by real-time fluorescent quantitative polymerase chain reaction (PCR), and the relationships between expression level of AMPD1 in serum of PTC patients and clinicopathological factors as well as prognosis were analyzed. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Luo et al (2018) identified that AMPD1 was closely associated with the survival of breast cancer patients. Zha & Wu (2018) found that the expression of AMPD1 in serum of patients with papillary thyroid carcinoma is closely related to the malignant evolution of PTC and clinical prognosis of patients. The relationship between AMPD1 and LUAD has not previously been elucidated.…”
Section: Discussionmentioning
confidence: 96%
“…Luo et al (2018) identified that AMPD1 was closely associated with the survival of breast cancer patients. Zha & Wu (2018) found that the expression of AMPD1 in serum of patients with papillary thyroid carcinoma is closely related to the malignant evolution of PTC and clinical prognosis of patients. The relationship between AMPD1 and LUAD has not previously been elucidated.…”
Section: Discussionmentioning
confidence: 96%
“…AMPD1, a metabolism-related gene, encodes adenosine monophosphate deaminase. Recent studies suggest that AMPD1 is closely associated with the prognosis of tumors [ 40 , 41 ]. However, the role of AMPD1 in UC or other inflammatory bowel diseases was not previously been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, AMPD1 can be used as a clinical molecular marker to judge the prognosis of patients, and even become a new therapeutic target. [23] . ENPP1 has been found to be related to the stemness of tumor cells in cancers such as breast cancer and glioblastoma, and is involved in tumor occurrence, nausea growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%